2020
DOI: 10.1007/s12053-020-09847-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating UK consumers’ heterogeneous engagement in demand-side response

Abstract: Demand-side response (DSR), the incentivised time-shifting of energy use by consumers away from peak times, is regarded as a potentially effective measure to balance electricity supply and demand. This will be even more important in the low-carbon energy system of the future, with a high share of nondispatchable power, such as variable renewable energy and nuclear power. Most DSR programmes require consumers' active engagement in shifting end-use activities. Previous studies have, however, rarely revealed soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In order to consider the possible role DSR could play in reducing grid impact of PV at a local level, two hypothetical DSR scenarios are considered based upon between 50% (DSR50) and 100% (DSR100) of households participating in DSR measures (smart dishwasher, washing machine, and tumble drier) by 2030 (Figure 3d). A recent nationwide survey indicates that around 50% of the UK population would be willing to shift times of dishwashing and laundry, indicating that the first of these scenarios could be achievable without substantial changes in attitudes (56). Modelled impacts of these measures on power demand are as described in references (57,58).…”
Section: Design Of Distributed Pv Load Growth and Flexibility Scenarios And Application To Simulated Networkmentioning
confidence: 99%
“…In order to consider the possible role DSR could play in reducing grid impact of PV at a local level, two hypothetical DSR scenarios are considered based upon between 50% (DSR50) and 100% (DSR100) of households participating in DSR measures (smart dishwasher, washing machine, and tumble drier) by 2030 (Figure 3d). A recent nationwide survey indicates that around 50% of the UK population would be willing to shift times of dishwashing and laundry, indicating that the first of these scenarios could be achievable without substantial changes in attitudes (56). Modelled impacts of these measures on power demand are as described in references (57,58).…”
Section: Design Of Distributed Pv Load Growth and Flexibility Scenarios And Application To Simulated Networkmentioning
confidence: 99%
“…Referring to socio-psychological theories, the psychological barriers to behavior change include: action inertia, social norms, emotion, perceived behavioral control, delay discounting and habit [64]. Additionally, socio-demographic factors such as, age, gender, location, education, household size, income and working situation can limit an individual's ability to change [47,70,150]. This reiterates the complexity of the way individuals live and make decisions.…”
Section: Barriers To Behavior Changementioning
confidence: 99%
“…The study showed Danish households were restricted by institutional rhythms while Pakistani households had a different administrative set up involving household staff compared to the typical nuclear families in Denmark [68]. Domestic cleaning practices have been targeted by research in assessing the flexibility of such practices within the household [70]. These practices include using the dishwasher and washing machine, a practice which involves a technological medium and is potentially highly flexible [105].…”
Section: Energy Practices and Demand Managementmentioning
confidence: 99%
“…The TOU policy is set based on the supply and demand relationship of the load. In fact, the TOU effect is closely related to consumers' willingness to participate actively [21]. The activities of household energy consumption mainly include cooking, dishwashing, laundry, heating, and bathing.…”
Section: Introductionmentioning
confidence: 99%